Friendship, joy, and physical fitness of elementary school students: outcome-based macro evaluation of physical education in Madura Island - Jufri, Arief Wildan; Rosidi, Sakban; Purwati, Titik (CV. Media Digital Publikasi Indonesia, 2023)
The lack of information regarding the benefits of physical education in primary education (SD/MI) in Madura Island resulted in its potential value not being fully realized. In addition, the existence of physical education is often seen as a peripheral or unimportant subject in the school curriculum. Meanwhile, outcomes, which are evaluations at the social or community level, often need to be thoroughly explored. The benefits of physical education ideally are based on the criteria of friends, fun, and fitness. This study seeks information about interpersonal peacefulness, physical activity enjoyment, and physical fitness. The research method used is quantitative and correlational descriptive with a testing design using the discrepancy evaluation model. The respondents involved in this study are 523 students. The results show that the mean of interpersonal peacefulness among students and physical activity enjoyment has met the established criteria, while the mean of physical fitness of students has not met the established criteria. The three variables have a functional relationship with a significant value <0.05. Recommendations that can be given to physical education teachers are to pay more attention to the element of physical activity enjoyment in children. According to hedonism theory, behavioral learning theory, and perceptual theory, humans always seek and repeat any action that gives pleasure. So, if exercising brings joy, they will repeat the activity. The more joy, the more active they will be in exercising.